"Our Divided Society—A Challenge to Religious Education": REA's 1969 National Convention and the Opening Up of Brave Conversations about Race and Religion. Issue 3 (27th May 2019) - Gunn, Dennis
Abstract: The Religious Education Association (REA) selected as its theme for its 1969 National Convention, "Our Divided Society—A Challenge to Religious Education, " addressing, among other topics, issues of race and racism. Previously, the REA presented a mixed legacy in addressing racial injustice, remaining largely silent on such issues during the civil rights era of the 1950s and 1960s, unlike the National Council of Churches, which had taken a prophetic stance early on. Thus, the 1969 convention's theme opened up brave new spaces for the REA to address issues of race and racism in American society.